Electricity–gas multi-agent planning method considering users’ comprehensive energy consumption behavior - Liu, Wentao; Zhou, Baorong; Ou, Mingyu; Zhao, Wenmeng; Huang, Guanglei; Mao, Tian (Frontiers in Energy Research, 2024)
With the advent of the energy Internet and the swift growth of unified energy systems, the comprehensive energy demand of users has gradually become a problem that cannot be ignored for the planning of integrated energy systems. Aiming at this problem, this paper suggests a multi-agent planning approach for electricity and gas, considering users' holistic energy consumption behavior. Firstly, utilizing a combined subjective and objective weighting method, this study establishes a utility model for user energy consumption characteristics. The analysis of comprehensive energy consumption behavior is conducted through an evolutionary game. On this basis, the planning revenue model for electricity grid and gas network investors is formulated, and the game mechanism of different investors is analyzed. A dynamic game model of electricity-gas multi-agent planning considering comprehensive energy consumption behavior is proposed. Ultimately, the model is resolved using an iterative exploration approach. The validity and efficacy of the proposed method are confirmed through a simulation example.